A child's introduction to the environment the air, earth, and sea around us--plus experiments, projects, and activities you can do to help our planet! - Driscoll, Michael 1973- (Black Dog & Leventhal Pub., 2008)
Discusses a variety of environmental sciences topics, including global warming, food chains, and desertification, along with a collection of experiments and conservation activities.